2004
DOI: 10.1212/01.wnl.0000113757.34662.aa
|View full text |Cite
|
Sign up to set email alerts
|

Triflusal vs aspirin for prevention of cerebral infarction

Abstract: This pilot trial has not found differences between triflusal and aspirin in the prevention of vascular complications after TIA or ischemic stroke, although given the wide CI, potentially important group differences could not be ruled out. Triflusal may be associated with a lower risk of hemorrhagic complications. A larger, prospective clinical trial is necessary to verify these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 19 publications
0
44
1
Order By: Relevance
“…[560][561][562] A recent noninferiority trial failed to show that sarpogrelate was not inferior to aspirin. 560 Triflusal has been examined in several trials and has not been found to be superior to asprin.…”
Section: Newer Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…[560][561][562] A recent noninferiority trial failed to show that sarpogrelate was not inferior to aspirin. 560 Triflusal has been examined in several trials and has not been found to be superior to asprin.…”
Section: Newer Agentsmentioning
confidence: 99%
“…560 Triflusal has been examined in several trials and has not been found to be superior to asprin. 562 Cilostazol has FDA approval for treatment of intermittent claudication and is further along in its development as a stroke treatment. The effectiveness of cilostazol compared with aspirin (doses not specified) was examined initially in a randomized, double-blind pilot study that enrolled 720 patients with a recent ischemic stroke.…”
Section: Newer Agentsmentioning
confidence: 99%
“…This was a relatively small dose compared to a conventional dose for patients with cerebrovascular disease. 15,19) Thus, adding a small dose of triflusal increased the antiplatelet effect of aspirin in patients with coronary artery disease and this could be used effectively in patients who underwent high risk coronary interventions. Additional action mechanisms of triflusal beyond aspirin: Triflusal was also reported to increase nitric oxide production by neutrophil and endothelial nitric oxide synthase (eNOS) protein expression in neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…40 ), a multicentric pilot study, including 431 patients, and Triflusal Aspirin Cerebral Infarction Prevention (TACIP) (ref. 41 ), including 2113 patients.…”
Section: Triflusalmentioning
confidence: 99%
“…In a post hoc analysis, the overall incidence of major and minor hemorrhagic events was significantly lower in TRIF group (2.8%) than the ASA group (8.3%) (ref. 40 ). TRIF is being used in the above mentioned countries, especially in Spain, as an alternative to ASA in cases of ASA intolerance.…”
Section: Triflusalmentioning
confidence: 99%